"q-NAVI": A case of market-based implementation of structural health monitoring in Japan. Issue 1 (February 2021) - Kanda, Katsuhisa; Nakashima, Masayoshi; Suzuki, Yoshitaka; Ogasawara, Saori
In Japan, structural health monitoring (SHM) of building structures began in the 1950s, but, until recently, its widespread use was not realized. A new trend arrived a few years ago, and currently over 850 buildings have SHM systems installed. The most recent SHM systems have been installed voluntarily by owners in the private sector; that is, the major development of recent Japanese SHM has been based on market forces. This article reports on why SHM was not accepted widely in the past, what were the keys for change of the atmosphere, how the building owners evaluate SHM after it is deployed, and what tangible benefits the building owners realize by experience on SHM implementation. To investigate those, an SHM system named q-NAVI is introduced as an example. The system has been deployed for 450 buildings, and they experienced a few significant shakings from recent earthquakes. SHM is also found effective for acquiring information on the quantification of fragility curves for various nonstructural components, using the data samples collected in recent earthquakes.